Analysis of Students' Creative Thinking Skills and Learning Activities in Physics Learning Using the Project-Based Learning Model - Sapulete, Heppy (Journal of Science and Science Education, 2025)
Physics learning often faces challenges in improving students' creative thinking skills and learning activities, which tend to remain low. This presents a significant challenge for educators to identify effective learning models that foster both creativity and student engagement. This study aims to analyze students’ creative thinking skills and learning activities in physics learning using the Project-Based Learning (PjBL) model. The research subjects were 29 students of Class A at SMA A in Central Maluku Regency. The research employed a mixed-method approach with a one-group pretest–posttest design. Instruments included a test to measure creative thinking skills and observation sheets as non-test instruments to assess students’ learning activities throughout the learning process. Data were analyzed using descriptive quantitative methods in the form of percentages, and qualitative analysis in narrative explanation, supported by a t-test to determine significant differences between pretest and posttest results. The findings showed that 52.5% of students reached a fairly high level of creativity after implementing the PjBL model, with a significant increase in creativity test scores compared to before the intervention. Additionally, observations of learning activities indicated very high student engagement, particularly during presentations, with a percentage reaching 83.25%. These findings demonstrate that the Project-Based Learning model is effective in enhancing students’ creative thinking skills while also stimulating active participation in physics learning